Analisis Usaha Budidaya Ikan Nila (Oreocromis niloticus) Dengan Sistem Bioflok - Alvionita, Mita; Yunus, Rusmiyanti; Mulis, Mulis (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
Tilapia is a fish species in Indonesia with significant economic value. Tilapia cultivation has excellent prospects, both domestically and internationally, requiring effective measures to ensure production meets community standards. The prospects for developing tilapia cultivation are quite promising, as the low production costs of tilapia farming allow for higher profits. Biofloc technology is an alternative solution to the waste problem of intensive farming. This technology is highly advantageous because it not only reduces inorganic nitrogen waste from leftover feed and feces, but also provides supplemental protein feed for farmed animals, thereby increasing growth and feed efficiency.This study aims to analyze the benefits and factors that influence the success of tilapia biofloc cultivation in SikoFish Gorontalo. This study uses a quantitative method with data collection techniques through surveys and observations. The results of the study indicate that tilapia biofloc cultivation can generate profits of Rp. 180,585,000 / harvest with a return on investment of 1.14 years. Factors that influence the success of tilapia biofloc cultivation are location selection, container preparation, media preparation, seed preparation, seed distribution, feed management, water quality management, and floc density. Therefore, it is necessary to develop business and production cost efficiency to increase income and make tilapia biofloc cultivation viable.